2014
DOI: 10.18632/oncotarget.2856
|View full text |Cite
|
Sign up to set email alerts
|

ROS production, intracellular HSP70 levels and their relationship in human neutrophils: effects of age

Abstract: ROS production and intracellular HSP70 levels were measured in human neutrophils for three age groups: young (20-59 years), elders (60-89 years) and nonagenarians (90 years and older). Elders showed higher levels of spontaneous intracellular ROS content compared with young and nonagenarian groups, which had similar intracellular ROS levels. Zymosan-induced (non-spontaneous) extracellular ROS levels were also similar for young and nonagenarians but were lower in elders. However, spontaneous extracellular ROS pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…In human muscle, ageing is accompanied by a higher need of mitochondria to maintain the same respiratory capacity as in young people indicating decay in mitochondrial efficiency (Larsen et al, 2012). Although the role of mitochondria as the major source of intracellular ROS production in ageing has been questioned during the last years , most data suggest that there is an increase in oxidative damage in the elderly affecting senescence (Lu and Finkel, 2008), fertility declining (Benkhalifa et al, 2014), skin ageing (Kammeyer and Luiten, 2015), neutrophils' activity (Kovalenko et al, 2014) or skeletal muscle (McDonagh, 2016).…”
Section: Mitochondrial Activity and Turnover Are Affected During Ageingmentioning
confidence: 99%
“…In human muscle, ageing is accompanied by a higher need of mitochondria to maintain the same respiratory capacity as in young people indicating decay in mitochondrial efficiency (Larsen et al, 2012). Although the role of mitochondria as the major source of intracellular ROS production in ageing has been questioned during the last years , most data suggest that there is an increase in oxidative damage in the elderly affecting senescence (Lu and Finkel, 2008), fertility declining (Benkhalifa et al, 2014), skin ageing (Kammeyer and Luiten, 2015), neutrophils' activity (Kovalenko et al, 2014) or skeletal muscle (McDonagh, 2016).…”
Section: Mitochondrial Activity and Turnover Are Affected During Ageingmentioning
confidence: 99%
“…There are only few studies concerning this issue and they refer to monocytes [41], lymphocytes [23, 41] and granulocytes [28]. There was observed age-related raise in the basal level of HSP70 in monocytes and lymphocytes [41].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study, however, showed a significant age-related decrease in HSP70 levels in lymphocytes [23]. Studies performed on neutrophils did not expose any significant age-dependent changes in HSP70 basal content in the cells [28]. Since NK cells are associated with the process of healthy ageing, the preservation of NK cell function until very advanced age may contribute to longevity [12, 18, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is important to highlight that in neutrophils, for example, ROS are essential for pathogen destruction through phagocytosis and for robust inflammatory responses [141]. Interestingly, in the elderly (60-89 years), a positive correlation has been found between iHSP70 and spontaneous ROS production by neutrophils, but the same correlation has not been confirmed in nonagenarians (>90 years) [142]. The lack of a positive correlation between neutrophil HSP70 levels and ROS in the latter group might be associated with the longer lifespan of these specific people.…”
Section: Suppression Of the Heat Shock Response In Agerelated Degenermentioning
confidence: 99%